1998
DOI: 10.4102/jsava.v69i1.807
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lantana camara poisoning in a Boer goat kid : case report

Abstract: Acute <em>Lantana camara</em> poisoning in a Boer goat kid is described. The animal was part of a flock of boer goats that was introduced from the Kalahari thornveld, where the plant does not occur, to an area where the plant grew abundantly. At necropsy, the animal was severely icteric, dehydrated and constipated, with hepatosis, distention of the gall-bladder and nephrosis, but no skin lesions. Histopathological findings of the liver confirmed moderate hepatosis with single-cell necrosis and bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…This is contrary to findings in Kenya, where a number of calves, sheep and East African goats, on zero-grazing, were poisoned when inadvertently exposed to lantana (Munyua et al 1990). Similar reports from Zimbabwe (Obwolo et al 1990) and South Africa (Ide and Tutt 1998) have confirmed that lantana is toxic to goats. However, it is postulated that different L. camara varieties have different toxin levels (MD Day, Queensland Biosecurity, pers.…”
Section: Impacts Of Lantana Camarasupporting
confidence: 75%
See 1 more Smart Citation
“…This is contrary to findings in Kenya, where a number of calves, sheep and East African goats, on zero-grazing, were poisoned when inadvertently exposed to lantana (Munyua et al 1990). Similar reports from Zimbabwe (Obwolo et al 1990) and South Africa (Ide and Tutt 1998) have confirmed that lantana is toxic to goats. However, it is postulated that different L. camara varieties have different toxin levels (MD Day, Queensland Biosecurity, pers.…”
Section: Impacts Of Lantana Camarasupporting
confidence: 75%
“…This is exacerbated by the fact that lantana is highly toxic to livestock if consumed (Figure 7). Ingestion of lantana by livestock can cause liver, kidney and gall bladder damage, dehydration and hepatogenous photosensitivity (Black and Carter 1985;Kellerman and Coetzer 1985;Ide and Tutt 1998). Raw photosensitised areas are susceptible to blowfly maggots and bacterial infections, contributing to ill-health.…”
Section: Impacts Of Lantana Camaramentioning
confidence: 99%
“…Goats, which are browsers often thought to be more tolerant of noxious weeds, are quite susceptible to lantana. Similar fi ndings are reported for Boer goats in South Africa (Ide and Tutt 1998). Similar fi ndings are reported for Boer goats in South Africa (Ide and Tutt 1998).…”
Section: Distribution and Habitat-presumably Native Tosupporting
confidence: 88%
“…Furthermore, there is some evidence that certain animals will develop a taste for Lantana and actually eat it in preference to other plants. Sheep and goats are susceptible but are rarely naturally poisoned, although one incident in relocated goats has been reported (Ide and Tutt, 1998). The toxic principles are pentacyclic triterpene acids.…”
Section: Lantana Camaramentioning
confidence: 99%